Coarazuphium tapiaguassu (Coleoptera: Carabidae: Zuphiini), a new Brazilian troglobitic beetle, with ultrastructural analysis and ecological considerations - Pellegrini, Thais Giovannini; Ferreira, Rodrigo Lopes (Zootaxa, 2011)
Coarazuphium tapiaguassu sp. n. was collected in caves SL 30, SL 31 and SL 35 located in Curionópolis (Pará, Brazil). C. tapiaguassu is readily differentiated by the absence of setae on the dorsal surface of the head close to the posterior margin, as the other species of the gens show one, two or tree pairs of setae. Taxa of Coarazuphium exhibit advanced troglobiomorphic characters in comparison to other Brazilian cave beetles. Increased extra-optic sensory structures, presence of particular sensilla, and sensory and gustatory receptors are characters not detected under routine microscopy and thus require ultrastructural methods for their study. Similar analyses are needed in other epigean Zuphiini species for a better interpretation of their functional meaning.